Specific Problems of Cost Accounting in Agriculture - Kondraszuk, Tomasz (Specyficzne problemy rachunku kosztów w rolnictwie, 2011)
This paper presents specific problems of cost accounting in agriculture. The essence of the distinctiveness of agricultural activity lies in the biological nature of the carried out production and the dependence on natural environment. The valuation of biological assets by fair value that is required in agriculture accounts for the result on production, not on sales. This results in the necessity to review both the approach itself to calculating result categories, and the employed cost accounting methods. A properly constructed cost accounting system in agriculture should be, on the one hand, oriented on measuring the costs of operating management process and short-term profit maximisation (economic year), and on the other hand support the strategic management processes and maximise the value of an agricultural farm in the long term.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2011; Nr 177, s. 71-78
Keywords: agriculture; cost accounting; accounting; management